Gas Chromatographic-Mass Spectrometric Method for the Simultaneous Determination of Resveratrol Isomers and 2,4,6-Trihydroxyphenanthrene in Red Wines Exposed to UV-Light - Francioso, Antonio; Laštovičková, Lenka; Mosca, Luciana; Boffi, Alberto; Bonamore, Alessandra; Macone, Alberto (Journal of agricultural and food chemistry, 2019)
Resveratrol (3,5,4'-trihydroxystilbene) is one of the most abundant polyphenols in red grapes, and red wine represents one of the most important dietary sources of this compound. Although its beneficial properties on human health have been widely investigated over the last 30 years, very little is known about its derivatives. Resveratrol can indeed undergo glycosylation, oligomerization and, upon UV-light exposure, it can isomerize from the trans-to the cis-isomer, which can further cyclize to 2,4,6-trihydroxyphenanthrene (THP). Although the effects of THP on human health are not yet known, being a polycyclic aromatic hydrocarbon, it can be potentially harmful. Because no data about THP occurrence in plant food and beverages are available, a simple procedure based on liquid-liquid extraction and gas chromatography-mass spectrometry has been developed and validated for the simultaneous qualitative and quantitative analysis of trans-resveratrol, cis-resveratrol, and THP in red wine, before and after UV-light exposure.
Keywords: isomerie; resveratrol; Gas Chromatography-Mass Spectrometry; Phenanthrenes; Wine; Resveratrol; GC−MS; Isomerism; Ultraviolet Rays; fenantreny; plynová chromatografie s hmotnostně spektrometrickou detekcí; víno; Glycosylation; glykosylace; 2,4,6-trihydroxyphenanthrene; ultrafialové záření; red wine